(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The objective of this analytical document in to propose an idea of protecting the ancient knowledge of Yurt craftmanship, to personalize it with Kyrgyzstan and to use Yurt as a brand for all the Kyrgyz manufactured products especially for the marketing of export quality agriculture products. This proposal calls for a state level intervention which can ensure that the agriculture products of export quality as of beans from Talas Region of Kyrgyzstan should be exported by using Yurt as a logo on its packing so that the international market could recognize its origin and Kyrgyzstan could get better marketing benefits from it.